Personal Data Protection In The Digitization Of Notary Services And PPAT: An Analysis Of The Legal Responsibility Of Notaries/PPAT On The Security Of Client Data - Wirda Ningsih Octavia (Yayasan pendidikan dzurriyatul Quran, 2026)
The digitization of notary services and Land Deed Making Officials (PPAT) has brought significant transformation in public services in the legal sector, but at the same time has raised new challenges related to the protection of clients' personal data. This study analyzes the legal responsibilities of notaries and PPAT in securing clients' personal data in the digital era based on Law Number 27 of 2022 concerning Personal Data Protection. Using normative legal research methods with the approach of laws and regulations, cases, comparison, and theory, this study examines three main problem formulations: (1) how to regulate the legal responsibility of notaries/PPAT in protecting clients' personal data according to the PDP Law; (2) how to implement personal data protection in the practice of digitizing notary/PPAT services in Indonesia; and (3) how is the ideal concept of legal responsibility of notaries/PPAT that is balanced between digitization efficiency and personal data protection. The results of the study show that although the PDP Law provides a comprehensive legal framework, its implementation in the practice of notaries and PPAT still faces various technical, administrative, and legal understanding obstacles. This study recommends the need for harmonization of sectoral regulations, improvement of digital security infrastructure, and strengthening of supervisory mechanisms to ensure effective protection of personal data.